Descriptions of Lasiodiamesa bipectinata spec. nov. and Parochlus kiefferi (Garrett) Brundin (Diptera: Chironomidae). - Sæther, Ole A. (Contributions to Entomology = Beiträge zur Entomologie, 1967)
Descriptions of Lasiodiamesa bipectinata spec. nov. and Parochlus kiefferi (Garrett) Brundin are given. The phylogenetic position of the Podonominae and of the described species is discussed. Nomenclatural Acts bipectinata Sæther, 1967 (Lasiodiamesa), spec. n.